The intensive interaction handbook - Hewett, Dave; Firth, Graham; Barber, Mark; Harrison, Tandy (SAGE, 2012)
Intensive Interaction is a straightforward approach to teaching the fundamentals of communication to children and adults who have severe learning difficulties or autism, and who are still at an early stage of communication development. This book is a practical guide to help those wishing to implement Intensive Interaction in their setting, and it provides detailed advice and step-by-step guidance as well as a consideration of all the issues associated with carrying out this approach.